Leptin Concentrations in Maternal and Umbilical Cord Blood in Relation to Maternal Weight, Birth Weight and Weight of the Placenta - Ishrat, S; Rahman, MW; Rahman, MR; Hussain, MZ; Jahan, S (Bangladesh Journal of Obstetrics & Gynaecology, 2009)
Objective: Leptin is a hormone which regulates adipose tissue mass of the body. Substantial increase of leptin during pregnancy and detection of leptin and leptin receptor in placenta have led to the speculation that leptin is a gestational hormone with a possible role in regulation of fetal growth. The study was done to find out whether maternal and cord blood leptin correlate with birthweight and weight of the placenta. Materials and methods: A prospective cross sectional study was undertaken in the Department of Obsterics and Gynecology, Bangabandhu Sheikh Mujib Medical University from January 2005 to June 2005. The study was carried out on 39 pairs of mothers and newborns. Maternal venous blood was sampled just before delivery. Cord blood was obtained, birth weight and placental weight measurements were taken just after delivery of the baby. Serum leptin levels were measured by enzyme linked immunosorbent assay. Results: Maternal serum leptin was 24.50 ng/ml (range- 13.15-45.60 ng/ml) and cord serum leptin was 6.50 ng/ml (range- 2.02-12.30 ng/ml). There was no correlation between maternal leptin and birth weight or between maternal leptin and placental weight. Cord leptin was significantly correlated with birth weight but not with placental weight. There was no correlation between maternal and cord blood leptin. There was no significant gender differences in cord blood leptin concentrations. Conclusions: There may be an important role of leptin in regulation of fetal growth and development. Placenta may not be a major source of leptin in maternal and feto-placental circulation. Maternal leptin cannot be a reliable marker of fetal growth. Keywords: Serum leptin, birth weight, placental weight doi: 10.3329/bjog.v23i1.3049 Bangladesh J Obstet Gynaecol, 2008; Vol. 23(1) : 3-7